Juridic Review of the Rights of Children with Mental and Physical Disabilities to Rehabilitation - Wijaya, Alvian Dwiangga; Anggriawan, Teddy Prima (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2022)
According to the Big Indonesian Dictionary, people mean people who suffer (suffer) something. Meanwhile, disability means a condition (such as illness or injury) that damages or limits a person's mental and physical abilities; or being unable to do things the normal way. Persons with disabilities have the same position, rights and obligations as non-disabled people. Prior to the enactment of Law No.19/2011, Indonesia already had Law No. 4/1997 on Persons with Disabilities (Law No.4 / 1997). The establishment of Law No.4 / 1997 is still considered to have not answered various issues of respect, protection and fulfillment of the rights of persons with disabilities, so Law Number 8 of 2016 concerning Persons with Disabilities was born (Law No.8 / 2016). The purpose of this research is to find out more clearly and in detail how to fulfill the rights of children with mental and physical disabilities in obtaining rehabilitation based on a juridical review. The method used is normative juridical with a non-doctrinal approach that views law as the basis. The results of this study are in accordance with applicable laws in Indonesia, in this case it is appropriate for the government to pay more attention to or improve existing programs specifically for persons with disabilities so that their lives are guaranteed in accordance with existing laws. Keywords: Equality; Legal Protection; Rehabilitation